Auto ML (International Journal of Food and Nutritional Sciences, 2022)
In today’s world, every task has been automated by the power of technology and artificial intelligence[1]. With all this automation being part of human survival, it is even difficult for people to learn things and to implement the code from scratch to develop a machine-learning model for various applications[2]. Even though they want to implement from scratch, an abundant number of algorithms are available, which makes it far more difficult to choose the correct and appropriate algorithmic model for their data.